Early hyperactivity in lateral entorhinal cortex is associated with elevated levels of AβPP metabolites in the Tg2576 mouse model of Alzheimer’s disease - Xu, Wenjin (Exp Neurol, 2014)
Alzheimer’s disease (AD) is a neurodegenerative disorder that is the most common cause of dementia in the elderly today. One of the earliest symptoms of AD is olfactory dysfunction. The present study investigated the effects of amyloid β precursor protein (AβPP) metabolites, including amyloid-β (Aβ) and AβPP C-terminal fragments (CTF), on olfactory processing in the lateral entorhinal cortex (LEC) using the Tg2576 mouse model of human AβPP over-expression. The entorhinal cortex is an early target of AD related neuropathology, and the LEC plays an important role in fine odor discrimination and memory. Cohorts of transgenic and age-matched wild-type (WT) mice at 3, 6, and 16 months of age (MO) were anesthetized and acute, single-unit electrophysiology was performed in the LEC. Results showed that Tg2576 exhibited early LEC hyperactivity at 3 and 6 MO compared to WT mice in both local field potential and single-unit spontaneous activity. However, LEC single-unit odor responses and odor receptive fields showed no detectable difference compared to WT at any age. Finally, the very early emergence of olfactory system hyper-excitability corresponded not to detectable Aβ deposition in the olfactory system, but rather to high levels of intracellular AβPP-CTF and soluble Aβ in the anterior piriform cortex (aPCX), a major afferent input to the LEC, by 3 MO. The present results add to the growing evidence of AβPP-related hyper-excitability, and further implicate both soluble Aβ and non-Aβ AβPP metabolites in its early emergence.